Effect of Factor XIII-A Val34Leu Polymorphism on Myocardial Infarction Risk: A Meta-Analysis. (November 2014) - Chen, Fei; Qiao, Qi; Xu, Peng; Fan, Bing; Chen, Zaoping
The association between factor XIII-A (FXIII-A) Val34Leu polymorphism and myocardial infarction (MI) risk remained controversial. We performed a meta-analysis. Online databases were searched. Twenty-eight studies were included. The FXIII-A Val34Leu polymorphism was significantly associated with MI risk (odds ratio (OR) = 0.83, 95% confidence interval [CI] 0.76-0.91; P < .0001). This result remained statistically significant when the adjusted ORs were combined (OR = 0.77, 95% CI 0.65-0.92; P = .004). When stratifying for race, this polymorphism showed decreased MI risk in Caucasians. In the subgroup analysis by age group, significant associations were observed in early-onset patients and in late-onset patients. In the subgroup analysis by gender, there was a significant association in women but not in men. In the subgroup analysis stratified by smoking status, MI risk was decreased in both smokers and nonsmokers. This study suggested that FXIIIA Val34Leu polymorphism was a protective factor for MI in caucasians.